Model Pembelajaran Tahfidz Al-Qur’an di Indonesia, Iran, Turki, dan Arab Saudi - Lilik Ummi Kaltsum; Mundzier Suparta; Fuad Thohari; Khaeron Sirin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
This article is the result of a study that discusses the tahfidz al-Qur’an learning model that is applied in Indonesia, Iran, Turkey, and Saudi Arabia. In addition, this research also wants to formulate the characteristics of each tahfidz institution by exploring the similarities and differences of each of the tahfidz institutions in the four countries in applying the tahfidz learning model, including its strategies and methods. The results of the study concluded that methodologically, learning tahfidz Qur’an in Indonesia, Iran, Turkey, and Saudi Arabia has similarities in terms of the continuity of the scientific pathways of the al-Qur’an teachers or al-Qur’an guides to the Prophet. In addition, the learning method applied also has similarities between one institution or pesantren and institutions in these countries, where the method is applied in a strict and structured manner, namely the bi al-naẓar method or the qirā’ah method, the kitābah method, and the method. simā'i The four countries also apply the same model in learning, namely talaqqī-mushāfahah, where students must deposit their memorization to the teacher face to face and the teacher must pay attention to the students reading. A significant difference between the countries with regard to specific materials or inserts is the level of understanding of the memorized verses. This research was conducted directly in four countries, namely Indonesia, Iran, Turkey, and Saudi Arabia with a qualitative approach and analyzed descriptively-comparatively.